Toward Flexible Spintronics: Perpendicularly Magnetized Synthetic Antiferromagnetic Thin Films and Nanowires on Polyimide Substrates. (11th May 2016) - Vemulkar, T.; Mansell, R.; Fernández‐Pacheco, A.; Cowburn, R. P.
Abstract : The successful fabrication of ultra‐thin films of CoFeB/Pt with strong perpendicular magnetic anisotropy and antiferromagnetic interfacial interlayer coupling on flexible polyimide substrates is demonstrated. Despite an increased surface roughness and defect density on the polyimide substrate, magnetic single layers of CoFeB still show sharp coercive switching. Magnetic Kerr imaging shows that the magnetization reversal is dominated by a greater density of nucleation sites than the identical film grown on Si. These layers maintain their magnetic characteristics down to a radius of curvature of 350 ± µm. Further, antiferromagnetically (AF) Ruderman‐Kittel‐Kasuya‐Yoshida (RKKY) coupled bilayers of CoFeB were fabricated which are robust under bending and the coupling strength is successfully modulated via interlayer engineering. Finally, a perpendicular synthetic antiferromagnetic (SAF) thin film grown on a polyimide substrate is patterned into straight 10 µm long nanowires down to 210 nm in width that displayed the robust switching characteristics of the thin film. These are extremely promising results for the fabrication of robust, flexible, magneto‐electronic, non‐volatile memory, logic, and sensor devices. Abstract : Perpendicular magnetic anisotropy (PMA) thin films with interlayer exchange coupling are technologically relevant for the next generation of magnetic memory and logic devices. Despite the extreme sensitivity of the magnetic properties to substrate roughness conditions, PMA CoFeB single magnetic layers, and synthetic antiferromagnetic thin films and nanowires, are successfully fabricated on polyimide substrates, and are magnetically robust under bending.